Prevalence of postpartum complications and associated factors among postpartum women in Uganda, a cross-sectional study - Namutebi, Mariam; Nalwadda, Gorrette K; Kasasa, Simon; Muwanguzi, Patience A; Kaye, Dan K (BioMed Central, 2024)
Postnatal care exhibits the lowest coverage levels in the obstetric continuum of care. The highest rates of maternal and newborn morbidity and mortality occur within 24 h of birth. Assessment of women in this time period could improve the detection of postpartum complications and maternal outcomes. This study determined the patterns of maternal assessment and the factors associated with postpartum complications.BACKGROUNDPostnatal care exhibits the lowest coverage levels in the obstetric continuum of care. The highest rates of maternal and newborn morbidity and mortality occur within 24 h of birth. Assessment of women in this time period could improve the detection of postpartum complications and maternal outcomes. This study determined the patterns of maternal assessment and the factors associated with postpartum complications.This was a cross-sectional study involving observations of immediate postpartum care provided to women following uncomplicated vaginal births at three health facilities in Mpigi and Butambala districts (Uganda) from November 2020 to January 2021. Data were collected using an observation checklist and a data abstraction form for maternal and newborn social demographic data. The collected data were analyzed using Stata version 14.0. Maternal assessment patterns were summarized as frequencies, and the prevalence of postpartum complications was calculated. Logistic regression analysis was performed at both bivariate and multivariate levels to identify factors associated with developing postpartum complications among these women.METHODSThis was a cross-sectional study involving observations of immediate postpartum care provided to women following uncomplicated vaginal births at three health facilities in Mpigi and Butambala districts (Uganda) from November 2020 to January 2021. Data were collected using an observation checklist and a data abstraction form for maternal and newborn social demographic data. The collected data were analyzed using Stata version 14.0. Maternal assessment patterns were summarized as frequencies, and the prevalence of postpartum complications was calculated. Logistic regression analysis was performed at both bivariate and multivariate levels to identify factors associated with developing postpartum complications among these women.We observed 263 women receiving care at three health facilities in the immediate postpartum period. The level of maternal assessments was very low at 9/263 (3.4%), 29/263(11%) and 10(3.8%) within the first two hours, at three hours and at the fourth hour, respectively. The prevalence of postpartum complications was 37/263 (14.1%), with 67.6% experiencing postpartum hemorrhage (PPH), 13.5% having perineal tears, and 10.8% having cervical tears. Mothers who did not undergo a postpartum check in the first three hours (p = 0.001), those who were discharged after 24 h (p = 0.038), and those who were transferred to the postpartum ward after two hours (p = 0.001) were more likely to have developed postpartum complications.RESULTSWe observed 263 women receiving care at three health facilities in the immediate postpartum period. The level of maternal assessments was very low at 9/263 (3.4%), 29/263(11%) and 10(3.8%) within the first two hours, at three hours and at the fourth hour, respectively. The prevalence of postpartum complications was 37/263 (14.1%), with 67.6% experiencing postpartum hemorrhage (PPH), 13.5% having perineal tears, and 10.8% having cervical tears. Mothers who did not undergo a postpartum check in the first three hours (p = 0.001), those who were discharged after 24 h (p = 0.038), and those who were transferred to the postpartum ward after two hours (p = 0.001) were more likely to have developed postpartum complications.The maternal assessment patterns observed in the population were suboptimal. Women who were not assessed at the third hour and those transferred after two hours to the postnatal ward were more likely to have developed postpartum complications.CONCLUSIONThe maternal assessment patterns observed in the population were suboptimal. Women who were not assessed at the third hour and those transferred after two hours to the postnatal ward were more likely to have developed postpartum complications. MEDLINE - Academic